2021
DOI: 10.3390/genes12121988
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Reveals the Dynamic Response Mechanism of Pearl Millet Roots under Drought Stress

Abstract: Drought is a major threat to global agricultural production that limits the growth, development and survival rate of plants, leading to tremendous losses in yield. Pearl millet (Cenchrus americanus (L.) Morrone) has an excellent drought tolerance, and is an ideal plant material for studying the drought resistance of cereal crops. The roots are crucial organs of plants that experience drought stress, and the roots can sense and respond to such conditions. In this study, we explored the mechanism of drought tole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…This was discovered in rice. SVs may be valuable for identifying heterotic groups and choosing parental lines for the creation of hybrid crops, as shown by a previous research that was conducted on 25 inbred lines of maize [33]. The study found parallels between PAVs and participation in heterotic groups.…”
Section: Genomics Regarding Milletsmentioning
confidence: 58%
“…This was discovered in rice. SVs may be valuable for identifying heterotic groups and choosing parental lines for the creation of hybrid crops, as shown by a previous research that was conducted on 25 inbred lines of maize [33]. The study found parallels between PAVs and participation in heterotic groups.…”
Section: Genomics Regarding Milletsmentioning
confidence: 58%
“…The bud stage is the most sensitive stage in plants under abiotic stresses, which could affect growth in later stages [ 38 ]. Drought stress limits the growth, development and survival rate of plants, leading to tremendous losses in yield, thus threatening global agricultural production [ 39 ]. In our study, 15% PEG was used to simulate drought stress [ 29 , 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Drought-exposed plants exert different mechanisms to regulate the responses to stress [ 39 ]. A 12 h duration under drought stress has been shown to be an optimal sampling time to study stress responses [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…We collected a total of 192 transcriptome data of accession Tifleaf 3 grown under abiotic stress conditions, including heat (Huang et al ., 2021 ; Sun et al ., 2021 ), drought (Ji et al ., 2021 ; Zhang et al ., 2021 ) and salt (Awan et al ., 2022 ) (Table S1 ). The 13‐day‐old pearl millet seedlings were grouped into the normal culture group (CK), heat treatment group (40 °C/35 °C), drought treatment group (20% PEG) and salt treatment group (100 mM/L).…”
Section: Methodsmentioning
confidence: 99%
“…The broad application of high‐throughput sequencing technologies has enabled the genomes of millets to be deciphered (Varshney et al ., 2017 ) and a large number of multi‐omics data from millets have been reported. For instance, intensive research on stress‐related genetic resources of millets has produced enormous data covering transcriptome sequencing (Awan et al ., 2022 ; Huang et al ., 2021 ; Ji et al ., 2021 ; Sun et al ., 2021 ; Wu et al ., 2021 ; Zhang et al ., 2021 ), whole‐genome resequencing (Varshney et al ., 2017 ) and phenomics (Varshney et al ., 2017 ). These offer new opportunities to innovate knowledge regarding plant abiotic stress tolerance and to advance the genetic improvement of stress tolerance in major crops.…”
Section: Introductionmentioning
confidence: 99%